The dimension of the effects of the arbitral agreement on non-signatories. Reflections on the treatment of the new Peruvian arbitration ac - Amprimo Plá, Natale (2020)
The arbitration agreement is the cornerstone of any and all arbitration proceedings; and, with the aim of proving its existence, the majority of the different rules that regulate arbitration proceedings in the world require that the referred agreement be in writing. However, the modalities for the fulfillment of this requirement have been gradually extended, to such a point that presently, there is no discussion about the fact that any means that produces a «testimony of the agreement» is enough for it to be considered fulfilled. Independently from these modalities, there are cases in which, both the doctrine and case law admit that those individuals who are not a party, in the strict sense, to the arbitration agreement, are obliged to participate in the arbitration proceeding. The Peruvian legislator adopts an innovative option of this possibility in the Peruvian Arbitration Law (Article 14 of Legislative Decree No 1071).